Anti-angiogenic effect of YuXueBi tablet in experimental rheumatoid arthritis by suppressing LOX/Ras/Raf-1 signaling. (15th November 2022) - Su, Xiaohui; Yuan, Bei; Tao, Xueying; Guo, Wanyi; Mao, Xia; Wu, Anguo; Wang, Qian; Liu, Chunfang; Zhang, Yanqiong; Kong, Xiangying; Han, Lan; Lin, Na
Abstract: Ethnopharmacological relevance: A Chinese patent medicine derived from a classical traditional Chinese medicine formula, Yu-Xue-Bi tablet (YXB) is widely used in the clinic to treat rheumatoid arthritis (RA). During the progression of RA, angiogenesis plays a central role in fostering the production of inflammatory cells, leading to synovial hyperplasia and bone destruction. However, whether YXB attenuates the angiogenesis during RA progression remains to be defined. Aim of the study: We aimed to evaluate the anti-angiogenic activity of YXB and explore its mechanism of action in collagen-induced arthritis (CIA) rats and VEGF-induced HUVECs. Materials and methods: Transcriptional regulatory network analysis and a network pharmacology approach were employed to explore mechanism of YXB in RA angiogenesis. The antiarthritic effect of YXB was evaluated by determining the arthritis incidence, and score, and by micro-CT analysis. The anti-angiogenic effect of YXB in vivo was assessed by histological and immunohistochemical analyses. The anti-angiogenic effect of YXB in vitro was assessed by wound healing, Transwell migration, Transwell invasion, and tube formation assays. Western-blotting and immunohistochemical analysis were employed to explore the molecular mechanisms of YXB. Results: YXB reduced disease severity and ameliorated pathological features in CIA rats. YXB markedly decreased bone destruction and synovial angiogenesis. Consistently, we also demonstrated that YXB effectively suppressed angiogenesis marker CD31 and VEGF expression. In vitro, YXB effectively inhibited HUVEC migration, invasion, and tube formation. Following the identification of transcriptional expression profiles, "YXB putative targets–known RA-related genes–genes associated with the therapeutic effect of YXB" interaction network was constructed and analyzed. After that, the LOX/Ras/Raf-1 signaling axis, which is involved in RA angiogenesis, was identified as one of the candidate mechanisms of YXB against RA. Experimentally, YXB dose-dependently decreased the expression levels of LOX, Ras, and Raf-1, as well as the phosphorylation of MEK and ERK in CIA rats, and these effects were better than the inhibitory effects of methotrexate (MTX), an FDA approved drug used for some autoimmune diseases such as RA. In addition, YXB may function as a potent angiogenesis inhibitor and significantly suppress the VEGF-induced activation of LOX/Ras/Raf-1 signaling in vitro . Conclusions: We provide evidence that YXB may decrease the disease severity of RA and reduce bone erosion by suppressing angiogenesis via inhibition of LOX/Ras/Raf-1 signaling. Graphical abstract: Image 1 Highlights: YXB might attenuate the severity of rheumatoid arthritis by blocking angiogenesis. YXB might suppress RA synovial angiogenesis via suppressing the LOX/Ras/Raf-1 signaling pathway. YXB may represent a promising antiangiogenic candidate drug for the treatment of RA in the future.